2006
DOI: 10.1109/tip.2005.864236
|View full text |Cite
|
Sign up to set email alerts
|

An efficient content-adaptive motion-compensated 3-D DWT with enhanced spatial and temporal scalability

Abstract: We propose a novel, content adaptive method for motion-compensated three-dimensional wavelet transformation (MC 3-D DWT) of video. The proposed method overcomes problems of ghosting and nonaligned aliasing artifacts which can arise in regions of motion model failure, when the video is reconstructed at reduced temporal or spatial resolutions. Previous MC 3-D DWT structures either take the form of MC temporal DWT followed by a spatial transform ("t+2D"), or perform the spatial transform first ("2D + t"), limitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…It is observed that in most of the test videos, more than 80% of blocks remain stationary. In a region where there is no motion, the TF results in zero energy in high frequency frame [3].…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is observed that in most of the test videos, more than 80% of blocks remain stationary. In a region where there is no motion, the TF results in zero energy in high frequency frame [3].…”
Section: Motivationmentioning
confidence: 99%
“…It was soon realized that, in order to fully exploit inter-frame redundancy, the temporal part of the transform must compensate for motion between frames that is referred as motion-compensated temporal filtering (MCTF). Without motion compensation a 3D DWT is a separable transform and the order of spatial and temporal DWT stages can be interchanged without altering the final subband [3]. However, this commutative property is lost, with the introduction of motion compensation, as the DWT is not shift invariant.…”
Section: Introductionmentioning
confidence: 99%
“…This improvement attributes to that the full-resolution reconstruction frames comprise higher frequency information. By using the information from higher frequency spatial-subbands, the type II leakage exists in reducedresolution layer can be compensated [2].…”
Section: Full-resolution Wz Decoding 1) Low-pass Subbands Decodingmentioning
confidence: 99%
“…However, the DWT is not a shift invariant operator. Compared to RDWT, spatial domain motion compensation is usually able to yield the better prediction efficiency for side information [2].…”
Section: Introductionmentioning
confidence: 99%
“…Lifting based MCTF performs wavelet transform in two sequential steps, the prediction and the update steps. In our experiments, the bidirectional 5/3 wavelet is used due to its better complexityefficiency trade-off comparing to other wavelet transforms [9]. The prediction and update steps for 5/3 lifting are:…”
Section: Background On Mctfmentioning
confidence: 99%